Peasant organization when faced with violence and capitalist objectification: The case of Sanzekan Tinemi in Guerrero, Mexico - Fini, Daniele (DIXI, 2020)
Objectives: The article presents a study on working conditions in a social economy under violent conditions that bring together peasants from the state of Guerrero, Mexico.Methodology: The information comes from qualitative research carried out with members of the organization. A theoretical approach inspired by Marxism and poststructuralism is adopted that, on the one hand, understands peasant labor and its relationship with the surrounding dominant capitalist processes and, on the other hand, assumes the reciprocal tension between the conditioning of power structures over subordinate subjects and the ability of the latter to adapt to and modify such structures. Results: The results of the research show the advances and limits of the associative experience of Sanzekan Tinemi with respect to offering decent working and living conditions to its members. It also shows the mul-ti-jobbing character of the work as well as of its relationship with the legal and regulatory environment in which it operates.Conclusions: Finally, some heuristic insights are presented which, through the Marxist position of reification, seek to theoretically pose the possibility of capturing the relations of domination and unequal appropriation to which peasant labor is subordinate.
Keywords: peasantry; capitalism; social economy; neoliberalism; labor